Comparison of different feedback controllers on an airfoil benchmark - L. Michel; C. Braud; J.-P. Barbot; J.-P. Barbot; F. Plestan; D. Peaucelle; X. Boucher (Wind Energy Science)
The present paper proposes a comparison of three well-established controllers: a robust proportional–integral–derivative (PID) controller (Conord and Peaucelle, 2021), a model-free control (Fliess and Join, 2013, 2022) and an adaptive sliding-mode control based on the super-twisting algorithm (Shtessel et al., 2023). The benchmark considered is an airfoil section equipped with trailing edge jets, load sensors and a perturbation system. The objective is to track the lift command under external wind perturbations. The outcome of this work is the comparison of performances for three control laws that are suitable when little knowledge is known from the physics. This study quantifies performance not only in terms of load control, but also in the needed implementation effort.